Systemic Means of Persuasion and Argument Evaluation: Insights From the Corpus of Competitive Debates - Będkowski, Marcin; Rogowska, Kinga J. (Informal Logic)

(untitled) (Informal Logic, 2024)
The paper discusses the role of systemic means of persuasion in argument evaluation. The core class of systemic means of persuasion is regress stoppers, whose fundamental function is to halt the infinite regress of justification by making claims more acceptable. The paper explores how systemic means of persuasion relate to the structure of arguments in the Toulmin model and function as persuasion cues that are typically processed heuristically. The study includes stylometric analysis and statistical data from three corpora, revealing these means as complementary to explicit argumentation. Observations and examples are drawn from an original corpus of competitive debates.